Investimento materno em anfíbios anuros: a questão da variação no tamanho do ovo - Cholak, Luiza Rieder [UNESP] (2015)
Reproduction is an essential process in organism's life history, although very costly in terms of physiology and ecology. An individual's reproductive success depends on many factors, such as viability, size and number of descendents produced. As time and energy are limited, there are trade-offs between components of life history, such as reproductive investment and survivorship, number and size of offspring, among others. Offspring fitness and survivorship are extremely dependent on the amount of resources available during development, especially in the initial phases. Thus, some models have been proposed trying to determine an ideal quantity of investment under certain conditions, considering that offspring environment is crucial in the initial phases, as offspring is more vulnerable to variations in biotic (predation, competition) and abiotic factors (temperature, precipitation). During the initial phases of development, parental influence is of extremely importance for descendants' survivorship and fitness, and may happens in the form of parental care, if any, and as yolk investment. Maternal investment may exhibit phenotypic plasticity, influencing offspring traits of adaptive significance, such as body size and capacity of escaping from predators. In this relationship between mother and offspring, there is a trade-off between the amount of resources she will invest without decreasing her own fitness. Females may allocate energy in different ways, such as producing many small eggs or few large ones. Another strategy is to invest differentially among eggs of the same clutch, or among clutches of the same female, or clutches of females from the same population. This differential investment may provide adaptive advantages in unpredictable environments, as a bet-hedging strategy, allowing females to diminish fitness variation along time. As anurans, in general, have an amphibian life cycle, with at least one aquatic phase, and many ...